A profile of drug utilization among elderly inpatients admitted at a tertiary level hospital in Bangalore: A prospective study - Mahboubeh Razavi; N K Meera; Hamed Karimian; Deepak Kumar Khajuria (Archives of Global Professionals, 2012)
Objectives: In the elderly population the aging process leads to physiological alterations, which makes these individuals more susceptible to chronic diseases and consequently, to increased drug utilization. The objective of the present study was to assess drug utilization profile and drug-drug interaction (DDI) in the elderly patients in a tertiary care hospital. Methods: A Hospital-based cross-sectional study was performed to examine pattern of drug use in elderly population aged 60 years and above on 250 inpatients from June 2010 till February 2011. The socio-demographic information of elderly inpatients, drug utilization patterns and DDI was studied. Results: A total of 2049 drugs were prescribed to 250 patients. Most of the geriatric patients were in age group of 60-65 years. Infectious diseases were the most common diagnosis made, followed by respiratory diseases and central nervous system disorders. The average number of drugs consumed by each patient was 8.19.